Implementasi Nilai-Nilai Pancasila Bagi Generasi Muda di Era Globalisasi - Sabian Nuraprilia; Dinie Anggraeni Dewi (STKIP PGRI SITUBONDO, 2021)
This research was conducted to find out, trace and examine more deeply about the implementation of Pancasila values ​​for the younger generation in the current era of globalization. This research study uses a qualitative method or a descriptive approach. The results of this discussion were obtained from the results of literature studies from various sources such as journals, books and articles. Then later results will be obtained about this implementation, which aims to find out whether the implementation of Pancasila values ​​in the younger generation in this era of globalization is going well or vice versa.